(untitled) (Sociología y tecnociencia, 2021)
The main purpose of this study was to analyze how the concept of state sovereignty is experiencing a crisis due to a major natural disaster. By using the illustration of the 2004 Aceh earthquake and tsunami, the concept of state sovereignty has been explored in the abnormal situation arising from the disaster as the state was unable to carry out its functions and authorities properly. This article used qualitative approach to explore the dynamic relations or network between agency (material or non-material, such as state, NGO, International organization, media, norms, military equipment, army, natural resources etc); which construct sovereignty assemblage. The territorialization and deterritorialization of sovereignty is investigated by seeing four dimensions proposed by Baker and McGuirk. This article demonstrates that sovereignty is very dynamic, and its definition is constructed and continuously through mechanisms engaging multiple actors and specific processes. This research found that the state conception of sovereignty before and after the disaster has been so dynamic, constructed and reconstructed overtime, which is influenced by the dimension of multiplicity, processualism, labor, and uncertainty.